2014
DOI: 10.1089/gtmb.2014.0193
|View full text |Cite
|
Sign up to set email alerts
|

Role of IFN-γ and IL-6 Cytokines and Their Association in Determining Susceptibility to Chronic Idiopathic Urticaria

Abstract: Chronic Idiopathic Urticaria (CIU) is a common skin disorder, which may occur spontaneously. The aim of the present study was to assess the serum levels of interferon (IFN)-γ and interleukin (IL)-6 and to examine the association of IFN-γ+874 T/A and IL-6-174 G/C cytokine gene polymorphisms. To accomplish this, ELISA-based cytokine serum levels of IFN-γ (n=30) and IL-6 (n=30) in CIU patients (n=100) and Healthy Controls (HC) (n=200) were performed. Amplification refractory mutation system-polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…31 IL-21 from the interleukin-2 family, in synergy with IL15 and IL18, can stimulate IFN-c production in T cells. [33][34][35] In the current study, positive ASST and/or positive SPT CSU have higher levels of IFN-c, IL-2 and IL-21, which can activate the basophils leading to a high CD63 expression. [33][34][35] In the current study, positive ASST and/or positive SPT CSU have higher levels of IFN-c, IL-2 and IL-21, which can activate the basophils leading to a high CD63 expression.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…31 IL-21 from the interleukin-2 family, in synergy with IL15 and IL18, can stimulate IFN-c production in T cells. [33][34][35] In the current study, positive ASST and/or positive SPT CSU have higher levels of IFN-c, IL-2 and IL-21, which can activate the basophils leading to a high CD63 expression. [33][34][35] In the current study, positive ASST and/or positive SPT CSU have higher levels of IFN-c, IL-2 and IL-21, which can activate the basophils leading to a high CD63 expression.…”
Section: Discussionmentioning
confidence: 51%
“…32 Synergistic effects of IFN-c, IL-2 and IL-21 display positive regulation of the molecular mediators in immune response and control of lymphocytemediated immunity. [33][34][35] In the current study, positive ASST and/or positive SPT CSU have higher levels of IFN-c, IL-2 and IL-21, which can activate the basophils leading to a high CD63 expression. This may be one of the reasons to explain why CSU patients with both allergen sensitization and serum autoreactivity had the highest level of CD63 expression.…”
Section: Discussionmentioning
confidence: 51%
“…38 TGF-β, which is implicated in urticaria pathogenesis, functions as an anti-inflammatory cytokine. Also, the expression of miR-194 and IFN-γ reduced while the expression of THBS1, TGF-β, Smad3, smad3 phosphorylation, and IL-4 promoted.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that IL-6 family of cytokines, may play an important role in pathogenesis of CSU [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%